Analytical performance and method comparison of a quantitative point-of-care immunoassay for measurement of bile acids in cats and dogs. (January 2021) - Weiler, Kristina; Kleber, Katharina; Zielinsky, Sabine; Moritz, Andreas; Bauer, Natali
Point-of-care analyzers (POCAs) for quantitative assessment of bile acids (BAs) are scarce in veterinary medicine. We evaluated the Fuji Dri-Chem Immuno AU10V analyzer and v-BA test kit (Fujifilm) for detection of feline and canine total serum BA concentration. Results were compared with a 5th-generation assay as reference method and a 3rd-generation assay, both run on a bench-top analyzer. Analytical performance was assessed at 3 different concentration ranges, and with interferences. For method comparison, samples of 60 healthy and diseased cats and 64 dogs were included. Linearity was demonstrated for a BA concentration up to 130 µmol/L in cats ( r = 0.99) and 110 µmol/L in dogs ( r = 0.99). The analyzer showed high precision near the lower limit of quantification of 2 µmol/L reported by the manufacturer. Intra- and inter-assay coefficients of variation were < 5% for both species and all concentrations. Interferences were observed for bilirubin (800 mg/L) and lipid (4 g/L). There was excellent correlation with the reference method for feline ( rs = 0.98) and canine samples ( rs = 0.97), with proportional biases of 6.7% and −1.3%, respectively. However, a large bias (44.1%) was noted when the POCA was compared to the 3rd-generation assay. Total observed error was less than total allowable error at the 3 concentrations. The POCA reliably detected feline and canine BA in clinically relevant concentrations.